2013
DOI: 10.1016/j.jad.2013.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genetic and environmental influences on trait anxiety from middle adolescence to early adulthood

Abstract: Background Middle adolescence to early adulthood is an important developmental period for the emergence of anxiety. Genetically-influenced stable traits are thought to underlie internalizing psychopathology throughout development, but no studies have examined changes in genetic and environmental influences on trait anxiety during this period. Method A longitudinal twin study design was used to study same-sex twin pairs (485 monozygotic pairs, 271 dizygotic pairs) at three ages, 14, 18, and 21 years, to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
(64 reference statements)
4
19
0
Order By: Relevance
“…Consistent with findings using Western samples (Franic et al 2010), no qualitative sex differences were found. As reported in the majority of previous studies (Legrand et al 1999;Scourfield et al 2003;Bartels et al 2004;Boomsma et al 2005;Lamb et al 2010;Zavos et al 2012;Garcia et al 2013) and in a meta-analysis (Burt, 2009), no quantitative sex differences were found in this study either, suggesting that boys and girls in the sample are generally influenced by the same genetic and environmental factors to the same degree, as reported similarly in two studies using Chinese samples (Unger et al 2011;Chen et al 2014). However, given the wide CIs that overlapped between MZ and DZ twins in males and females, respectively, correlations suggested that the significant genetic influences in anxiety in late childhood (10-12 years) Data are given as correlation (95% confidence interval).…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with findings using Western samples (Franic et al 2010), no qualitative sex differences were found. As reported in the majority of previous studies (Legrand et al 1999;Scourfield et al 2003;Bartels et al 2004;Boomsma et al 2005;Lamb et al 2010;Zavos et al 2012;Garcia et al 2013) and in a meta-analysis (Burt, 2009), no quantitative sex differences were found in this study either, suggesting that boys and girls in the sample are generally influenced by the same genetic and environmental factors to the same degree, as reported similarly in two studies using Chinese samples (Unger et al 2011;Chen et al 2014). However, given the wide CIs that overlapped between MZ and DZ twins in males and females, respectively, correlations suggested that the significant genetic influences in anxiety in late childhood (10-12 years) Data are given as correlation (95% confidence interval).…”
Section: Discussionmentioning
confidence: 58%
“…The substantial role of genes in the etiology of internalizing disorders is supported by evidence from twin and adoption studies (e.g., Ehringer, Rhee, Young, Corley, & Hewitt, 2006;Garcia et al, 2013;Tully et al, 2010), and research findings consistently support separate, though positively correlated, genetic loadings on these two subfactors (Kendler, Prescott et al, 2003). Tully and Iacono (2014) proposed an empirically derived model to explain the hierarchical factor structure of internalizing disorders.…”
Section: The Structure Of Internalizing Disordersmentioning
confidence: 98%
“…Another UK study estimated STAI TA heritability at 31%, with significant genetic correlations with state anxiety [Lau et al, ]. A study in US children found lower heritability for TA in early childhood (15%) that increased by late adolescence to 45% [Garcia et al, ]. A recent study in Chinese children (ages 9–18) reported heritability estimates of 50–60% for STAI TA [Chen et al, ].…”
Section: Resultsmentioning
confidence: 99%